Perceptions of Tax Corruption, Quality of Fiscus Service, Organizational Climate, Attitude of Fiscus, Taxpayer's Motivation and Taxpayer Compliance - Jeandry, Gregorius (AIBPM Publisher, 2023)
The purpose of this study is to determine the influence of perceptions of tax corruption, the quality of fiscus services, the organizational climate, the attitude of the fiscus, and the motivation of taxpayers on taxpayer compliance. The population in this study were individual taxpayers registered with the Ternate KPP with a sample of 93 respondents. The analysis tool used is multiple linear regression analysis using SPSS 26. The results showed that the organizational climate and motivation of taxpayers had a positive effect on taxpayer compliance, while the perception of tax corruption, the quality of fiscus services, and the attitude of fiscus did not affect taxpayer compliance.